2019
DOI: 10.1055/a-0991-0498
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Risk Factors for Periodic Limb Movements in a Large Cohort of Insomnia and Chronic Fatigue Patients

Abstract: Introduction Although the pathophysiology of periodic limb movements in sleep (PLMS) is not well understood, there is increasing belief that management of PLMS can modulate humans’ general health. The aim of this study is to investigate the associations between risk factors including the use of antidepressants, hypnotics, and antihistamines as well as of caffeine, alcohol, and nicotine and the occurrence of PLMS and periodic limb movement disorder (PLMD). Methods Patients with either chronic fatigue or insomni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Several psychotropic medications have been linked to PLMI above 15 events per hour (78). For example, whilst dopamine-receptor antagonists, anticonvulsants, and lithium can potentially precipitate PLMS symptoms, it is typically the antidepressants, including selective-serotonin reuptake inhibitors (SSRIs; including sertraline), tricyclic anti-depressants (TCA; e.g., amitriptyline), and serotonin and norepinephrine reuptake inhibitors (SNRIs; e.g., venlafaxine and mirtazapine) which have been linked to pharmacologically induced PLMs (77). However, several antidepressants have been identified that do not appear to precipitate PLMs and are hence clinically recommended in affected or vulnerable patients, namely trazodone, bupropion (134), nefazodone and doxepin (10,135).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Several psychotropic medications have been linked to PLMI above 15 events per hour (78). For example, whilst dopamine-receptor antagonists, anticonvulsants, and lithium can potentially precipitate PLMS symptoms, it is typically the antidepressants, including selective-serotonin reuptake inhibitors (SSRIs; including sertraline), tricyclic anti-depressants (TCA; e.g., amitriptyline), and serotonin and norepinephrine reuptake inhibitors (SNRIs; e.g., venlafaxine and mirtazapine) which have been linked to pharmacologically induced PLMs (77). However, several antidepressants have been identified that do not appear to precipitate PLMs and are hence clinically recommended in affected or vulnerable patients, namely trazodone, bupropion (134), nefazodone and doxepin (10,135).…”
Section: Risk Factorsmentioning
confidence: 99%
“…This finding is in keeping with a previous cohort study that demonstrated a decrease in PLMS and PLMD with benzodiazepines in a cohort of patients with insomnia and chronic fatigue. 11 Furthermore, 2 previous studies that compared clonazepam and a placebo also found a reduction in PLMS in the clonazepam group. 37,38 Another cohort study, however, did not find a significant association between benzodiazepine use and a PLMI greater than 15.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have also demonstrated an increased PLMI in association with SSRI and SNRI use. 9,11,27 The mechanism underlying this association has not been fully elucidated; however, previous studies have speculated that SSRIs and SNRIs may increase PLMS through a serotoninergic mediated increase in dopamine transporters ultimately leading to a subsequent decline in dopaminergic activity. [27][28][29] In addition, because SNRIs increase both norepinephrine and serotonin levels, prior research suggests that they may also increase PLMS through a norepinephrine-mediated increase in sympathetic nervous system activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations